Interleukin-1 receptor antagonist delivery through adenoviral mediated gene transfer as a treatment for equine joint disease - Frisbie, David D., author; McIlwraith, C. W., advisor; Chapman, Phillip L., committee member; Evans, C. H., committee member; Oxford, J. R., committee member; Trotter, G. W., committee member (Colorado State University. Libraries, 1999)
The interleukin-1 (IL-1) system is a small group of cytokines composed of two agonist proteins and a receptor antagonist (IL-1Ra). The action of the IL-1 system is mediated through binding of these ligands to the IL-1 receptors. Binding of the IL-1Ra protein to IL-1 receptors has not been associated with biological activity and serves to block the binding of the other ligands. The IL-1 system has a wide range of biological activities centrally involved in the genesis and maintenance of inflammatory responses. More specifically, it has been centrally linked to mediation of joint pathology in most species. This project was conducted to assess both ability to deliver a transgene to the joints of horses, and the specific effects overproduction of IL-1Ra using gene transfer would have on an experimental model of joint disease in the exercising horse. Using the published gene sequence for equine IL-1Ra, an adenoviral vector (Ad-EqIL-1Ra) was constructed that was capable of equine IL-1Ra transgene expression. This vector was tested in vitro to ensure its ability to both transduce equine synoviocytes without cytotoxic effects and produce a biologically active IL-1Ra molecule. A dose titration of the vector was conducted in vivo, in the equine metacarpal and intercarpal joints, to ascertain the concentration of vector that produced the highest transgene expression for the longest period of time without significant deleterious effects. The result of this in vivo work suggested a vector concentration of 20 X 1010 particles/joint met the defined criterion. Using an experimental model of equine joint disease, the ability of intra-articular (IA) administration of Ad-EqlL-1Ra to effect osteochondral fragment induced joint pathology was evaluated. This work demonstrated an approximately 28 day effective upregulation of IL-1Ra expression through IA administration of Ad-EqlL-1Ra. This increased level of IL-1Ra was associated with significant improvement in clinical parameters of pain and disease activity, as well as beneficial effects in histologic parameters measured from synovial membrane and articular cartilage. This study provided proof of principle that gene therapy, using a potentially anti-arthritic gene sequences, is possible and efficacious in the horse and will hopefully serve as a cornerstone in future equine therapeutics.
Keywords: surgery; neurology; animal diseases; neurosciences; medicine